2007
DOI: 10.1177/0145721707301371
|View full text |Cite
|
Sign up to set email alerts
|

The Development, Implementation, and Process Evaluation of the REACH Detroit Partnership's Diabetes Lifestyle Intervention

Abstract: A community-based, culturally tailored diabetes lifestyle intervention delivered by trained community residents was associated with high participant satisfaction and retention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
109
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(114 citation statements)
references
References 27 publications
2
109
1
Order By: Relevance
“…Staff and participant insight-Participant insight, across all 12 interventions, was consistently reported as satisfactory, especially among those attending group sessions [28,33,38]. End of study feedback found that group sessions allowed social interaction, discussion of ideas, help from other adults with diabetes and feelings of not being alone.…”
Section: Potentially Relevant Citations Identified (N=3237) Electronimentioning
confidence: 96%
See 4 more Smart Citations
“…Staff and participant insight-Participant insight, across all 12 interventions, was consistently reported as satisfactory, especially among those attending group sessions [28,33,38]. End of study feedback found that group sessions allowed social interaction, discussion of ideas, help from other adults with diabetes and feelings of not being alone.…”
Section: Potentially Relevant Citations Identified (N=3237) Electronimentioning
confidence: 96%
“…The remaining collection was further analysed in-depth and a total of 12 articles, which reported detail relating to the process of intervention delivery, were included in the final analysis [28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Articlesmentioning
confidence: 99%
See 3 more Smart Citations